The book of thorns - Fox, Hester (Graydon House, 2024)
When Cornelia joins Napoleon's army as a traveling naturalist with the power to heal, she meets the sister she never knew existed on the opposite side of the battlefield and together, they must use the magic of flowers to solve the mystery of their mother's death, while fighting for their survival.